The Islamic FIQH Council of the Muslim World League - Akoridis, Modi Suleman (Politikologija religije, 2022)
The Islamic Fiqh Council is considered to be one of the most important organs of the Muslim World League (MWL), and it serves as the legal body that directs the League's work in general, especially in religious and jurisprudential issues. It also serves as the Saudi version of the specialized fiqh councils distributed in most countries of the Muslim world. The Council's work extends to many fields including issuing decrees and publishing dictionaries and academic works. In this paper, the researcher tries to introduce the Islamic Fiqh Council, its history, its organs, the tasks it manages and the most important issues it discusses, as well as the general religious line it follows. The researcher has relied almost entirely on the Council's publications and periodicals due to the lack of studies devoted to studying the Council.